Assessment of Protein and Fiber Content of Kansas Grasslands Enrolled in the Conservation Reserve Program - Jason M. Warner (Kansas Agricultural Experiment Station Research Reports, 2026)
Objective: To measure the nutrient content of standing Conservation Reserve Program (CRP) forages in Kansas throughout the year. Study Description: Standing forage samples (n = 294) were collected from 25 sites across 16 counties over two years in Kansas by Extension agents and Beef Cattle specialists. Samples were classified as eastern or northwestern Kansas based on the site location and were collected monthly to determine composition change throughout the year. All samples were analyzed for crude protein, total digestible nutrients, calcium, and phosphorus. The Bottom Line: The nutrient composition data for CRP forages can be used by producers to make informed management decisions when CRP is released for haying or grazing, which is critical, as previous assessments of CRP forage quality throughout Kansas are not widely available.
Keywords: conservation; forage; quality